'Crazy-paving' pattern: an exceptional presentation of cryptogenic organising pneumonia associated with chronic obstructive pulmonary disease. (6th May 2016) - Kunal, Shekhar; Pilaniya, Vikas; Jain, Sudhir; Shah, Ashok
Abstract : Organising pneumonia (OP) is a distinct but uncommon entity with characteristic clinicoradiological features and histological findings. When the aetiology of OP remains unknown, it is termed as cryptogenic OP (COP). COP is seen in the majority of patients with OP and usually observed in non/former smokers. A 54-year-old man, a smoker, presented with breathlessness, cough and mucoid sputum. Imaging demonstrated unilateral 'Crazy-paving' pattern in the left upper lobe and left-sided effusion. In addition, paraseptal emphysema and left lower lobe bullae along with very severe obstructive ventilatory defect and impaired diffusion suggested chronic obstructive pulmonary disease (COPD). Transbronchial biopsy was suggestive of OP. In the absence of a definite aetiology, a diagnosis of COP associated with COPD was established. COP presenting as a unilateral 'Crazy-paving' pattern is yet to be documented. To the best of our knowledge, this is the first detailed description of COP presenting as unilateral 'Crazy-paving' pattern associated with COPD.